2019
DOI: 10.1186/s13059-019-1684-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence analysis of a Pan African set of samples reveals archaic gene flow from an extinct basal population of modern humans into sub-Saharan populations

Abstract: Background Population demography and gene flow among African groups, as well as the putative archaic introgression of ancient hominins, have been poorly explored at the genome level. Results Here, we examine 15 African populations covering all major continental linguistic groups, ecosystems, and lifestyles within Africa through analysis of whole-genome sequence data of 21 individuals sequenced at deep coverage. We observe a remarkable correlation among genetic diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 80 publications
2
76
1
Order By: Relevance
“…We estimated that this introgression happened roughly 100,000 years before present and that the source hominin population diverged from anatomically modern humans about two million years before present. Other studies using sophisticated genome‐wide approaches, found concordant evidence of such haplotypes across the genome (Durvasula & Sankararaman, ; Lorente‐Galdos et al, ). A recent model‐based approach suggests that a population‐specific introgression(s) may have happened as recently as 30,000 years before present affecting ancestors extant African populations (Hsieh et al, ).…”
Section: What Is the Current View Of Human Evolutionary History From mentioning
confidence: 87%
See 1 more Smart Citation
“…We estimated that this introgression happened roughly 100,000 years before present and that the source hominin population diverged from anatomically modern humans about two million years before present. Other studies using sophisticated genome‐wide approaches, found concordant evidence of such haplotypes across the genome (Durvasula & Sankararaman, ; Lorente‐Galdos et al, ). A recent model‐based approach suggests that a population‐specific introgression(s) may have happened as recently as 30,000 years before present affecting ancestors extant African populations (Hsieh et al, ).…”
Section: What Is the Current View Of Human Evolutionary History From mentioning
confidence: 87%
“…It has been widely accepted that several hominin species have lived in Africa contemporaneously with anatomically modern humans (e.g., Homo naledi [Dirks et al, ]). Indeed, small but significant deviations from expected linkage disequilibrium and demographic trends invoke introgression from archaic hominin(s) in Africa (Durvasula & Sankararaman, ; Hammer et al, ; Hsieh et al, ; Lorente‐Galdos et al, ; Xu et al, ). A relative consensus of the admittedly small number of studies is that the source of this introgression is a now‐extinct hominin population that diverged from the modern human lineage between 0.5 and 2 million years before present.…”
Section: What Is the Current View Of Human Evolutionary History From mentioning
confidence: 99%
“…Numerous genetic variants associated with drug response and disease susceptibility have been identified in the past in different populations. Unfortunately, African populations are underrepresented in these studies despite most of the human genetic variation being present in Africa [1][2][3][4][5]9 . In this context, we have created a genome-wide and publicly accessible Somali dataset using Axiom PMRA SNP array.…”
Section: Discussionmentioning
confidence: 99%
“…the use of artificial neural networks (ANN), has only very recently been used to tackle population genetics questions. First, multilayer perceptron (MLP) were used to process large sets of summary statistics and to predict jointly selective sweeps and simple demographic changes (Sheehan and Song, 2016), or to disentangle between multiple scenarios of archaic introgression thanks to an additional ABC step (Lorente-Galdos et al, 2019, Mondal et al, 2019). A second type of ANN, convolutional neural networks (CNN), were then applied to summary statistics computed over 5Kb genomic regions in order to predict selective sweeps (Xue et al, 2019).…”
Section: Introductionmentioning
confidence: 99%